The firm-wage gender gap and formal sector churn over the life cycle - Ihsaan Bassier; Leila Gautham (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
We find that women sorting into lower wage firms explains nearly half of the gender wage gap in South Africa, using matched employer-employee panel data covering the universe of formal sector workers. Sorting varies considerably over the life cycle: the firm-wage gender gap is negligible for the youngest workers, grows steeply for 25-35-year-olds (i.e. typical child-rearing years), and narrows for older workers. The increase is driven by those continuously employed— while women are almost as likely as men to switch firms, men are more likely to switch to betterpaying firms, consistent with discrimination or non-wage amenities. Churn also contributes to the gap (though is relatively constant), since women enter formal employment at worse-paying firms than men. The importance of these two groups, the continuously employed versus entrants, depends on the size of the formal sector, thus linking the life cycle patterns underlying gender gaps with economic development.
Keywords: J31; J16; J42; J71; 330; firm wage premia; gender wage inequality; sorting; worker transitions